Cr in dredged marine sediments: Anthropogenic enrichment, bioavailability and potential adverse effects. Issue 1 (15th July 2017) - Baraud, Fabienne; Leleyter, Lydia; Lemoine, Mélanie; Hamdoun, Hakim
Abstract: This study focuses on chromium detected in 13 harbor sediments dredged across the English Channel. The total concentrations of Cr range from 5 to 61 mg kg − 1, which reveal no or low enrichment for 12 of the 13 samples, according the enrichment factor (EF) calculations. Sequential extraction procedure was applied to determine the mineralogical speciation of Cr, in order to assess its potential (re)mobilization to the aquatic environment. Cr is mainly associated to the residual fraction, then distributed in the oxydizable and reducible fractions. The possible relationships between the enrichment, mobility and possible biological effects (according calculation of Adverse Effect Index (AEI)) suggests possible toxicity incidence even for moderate enrichment. A link is observed with the oxydizable fraction (r = 0.8 and r = 0.5 respectively for EF and AEI). Highlights: Cr is analyzed in harbor sediments dredged across the English Channel. EF calculations reveal no or low enrichment for all the sediments studied. Possible relationships between EF, AEI and mobility are investigated.